Electromyographic responses during isometric contraction in post-activation potential protocol - Hacı Ahmet Taşpınar; Muhammet Emirhan Çelik; Necdet Apaydın; Hasan Sözen; Gökhan İpekoğlu; Tuğba Çetin (Turkish Journal of Kinesiology)
Post-activation potentiation (PAP) has recently emerged as a pivotal phenomenon representing an acute enhancement in performance by significantly increasing muscle strength. The aim of this study was to investigate the effect of PAP on the median and peak values of vastus lateralis, vastus medialis, and rectus femoris muscles during isometric muscle contraction using electromyography (EMG). The study involved 14 male amateur soccer players whose one-repetition maximum (1RM) values were determined in the initial session. A crossover design was employed, implementing both a PAP protocol consisting of one set of three repetitions at 85% of 1RM and a Non-PAP protocol consisting only of warm-up exercises. The median and peak values of maximal voluntary contraction (MVC) between groups (Non-PAP and Back-squat) were compared, employing the Mann-Whitney U test for intergroup comparisons. The results indicated no statistically significant differences in the median and peak values of the vastus lateralis, vastus medialis, and rectus femoris muscles between the Non-PAP and Back-squat groups. However, upon closer examination, it was observed that the median and peak EMG responses of the PAP group were higher compared to the Non-PAP group. These findings suggest that while PAP may not produce statistically significant changes in muscle activation in a small sample, there may still be a practical increase in muscle response following PAP, highlighting its potential benefit in enhancing performance.